Validating the trauma care system developed by Yokohama City local government. Issue 1 (19th April 2022) - Takeuchi, Ichiro; Morimura, Naoto; Iwashita, Masayuki; Kitano, Mitsuhide; Doi, Tomoki; Hayashi, Munetaka; Fujita, Takashi; Yamasaki, Motoyasu; Shuri, Jun
Abstract : Background: Since becoming the city with the first government‐designated major trauma center in 2014, Yokohama has been striving to centralize care for extensive trauma patients. Hence, in this study, the Yokohama City Major Trauma Care Advisory Committee tested the efficacy of the centralization of care for trauma patients. Methods: This investigation included all cases of deaths due to road traffic accidents that occurred in the 2‐year period following the establishment of the major trauma center. The probability of survival was calculated using data provided by the police and fire departments. Cases that died despite having a probability of survival of 50% or more were included in the survey undertaken by physicians recommended by the Japanese Association for the Surgery of Trauma, who visited the hospitals. Results: Of those surveyed, preventable trauma death accounted for 1 case (1.7%) and potentially preventable trauma death accounted for 7 (11.9%), compared with 5 (9.8%) and 11 (21%) cases, respectively, in the period 2009–2010. Conclusions: Comparing the survey conducted before establishment of the major trauma center, those results support the benefits of centralizing care for severe trauma cases. We aim to continue improving trauma care provided through the center along with the Yokohama Medical Control Council and to overcome challenges that were identified through the peer review. Abstract : Centralization of Trauma care would be required in Japan.